Screening capacity of Geriatric Depression Scale with 10 and 5 items - Apóstolo, João; Bobrowicz-Campos, E.; Ivo Reis; Henriques, S.; Carla Correia (Referência: revista de enfermagem, 2018)
Background: The use of the brief versions of the Geriatric Depression Scale (GDS) for depression screening in different health care settings requires the identification of a cutoff. Objectives: To assess the screening ability of the GDS-10 and GDS-5 for depression using DSM-5 diagnostic criteria for major depressive episode as reference test. Methodology: The sample consisted of 139 older people. Sensitivity and specificity for different cutoff values were obtained using the Receiver Operating Characteristic curve. The cutoff was selected based on the Youden Index. Results: The optimal cutoff was 1/2 for both versions of the GDS. The GDS-10 showed a sensitivity of 100% and a specificity of 45.7%, and the GDS-5 showed a sensitivity of 78.3% and a specificity of 85.3%. Conclusion: The GDS-10 proved to be a good screening instrument for depression and its use in routine care is justifiable. The use of GDS-5 for screening depression is not recommended due to its limited screening ability.